High gastrointestinal permeability and local metabolism of naringenin: influence of antibiotic treatment on absorption and metabolism. Issue 2 (17th June 2015) - Orrego-Lagarón, Naiara; Martínez-Huélamo, Miriam; Vallverdú-Queralt, Anna; Lamuela-Raventos, Rosa M.; Escribano-Ferrer, Elvira
Abstract : The present study aims to determine the permeability of naringenin in the stomach, small intestine and colon, to evaluate intestinal and hepatic first-pass metabolism, and to study the influence of the microbiota on the absorption and disposition of naringenin (3·5 μg/ml). A single-pass intestinal perfusion model in mice ( n 4–6) was used. Perfusate (every 10 min), blood (at 60 min) and bile samples were taken and analysed to evaluate the presence of naringenin and its metabolites by an HPLC-MS/MS method. To study the influence of the microbiota on the bioavailability of naringenin, a group of animals received the antibiotic rifaximin (50 mg/kg per d) for 5 d, and naringenin permeability was determined in the colon. Naringenin was absorbed well throughout the gastrointestinal tract but mainly in the small intestine and colon (mean permeability coefficient 7·80 (sd 1·54) × 10 − 4 cm/s and 5·49 (sd 1·86) × 10 − 4 cm/s, respectively), at a level similar to the highly permeable compound, naproxen (6·39 (sd 1·23) × 10 − 4 cm/s). According to the high amounts of metabolites found in the perfusate compared to the bile and plasma, naringenin underwent extensive intestinal first-pass metabolism, and the main metabolites excreted were sulfates (84·00 (sd 12·14)%), followed by glucuronides (8·40 (sd 5·67)%). Phase II metabolites were found in all perfusates from 5 min of sampling. Mice treated with rifaximin showed a decrease in naringenin permeability and in the amounts of 4-hydroxyhippuric acid and hippuric acid in the lumen. Naringenin was well absorbed throughout the gastrointestinal tract and its poor bioavailability was due mainly to high intestinal metabolism.